Impact of tamarind seed gum on the viscosity behavior, thermal properties, and extrusion characteristics of native corn starch. Issue 4 (8th March 2023) - Wagner, Caleb E.; Richter, Jana K.; Dey, Debomitra; Finnie, Sean; Ganjyal, Girish M.
Abstract : Abstract: Tamarind seed gum (TSG) is a cold‐swelling hydrocolloid with remarkable processing stability and starch synergy. Its use in direct expanded extruded foods has not been documented. The thermal and pasting viscosity properties of six TSG (0%, 0.5%, 1.0%, 2.5%, 5.0%, and 7.5% TSG) and native corn starch blends were characterized by differential scanning calorimetry and ViscoQuick, respectively. These same blends were extruded using a corotating twin‐screw extruder at four screw speeds (SSs) (150, 300, 450, and 600 rpm). System back pressure, motor torque, and specific mechanical energy (SME) were measured. Extrudate quality metrics, such as expansion ratio (ER), water absorption index (WAI), and water solubility index (WSI), were also measured. The pasting viscosities indicated that TSG inclusion increases viscosity but also makes the starch‐gum paste more susceptible to permanent shear degradation. The thermal analysis indicated that TSG inclusion narrowed the melting endotherms and lowered the energy required for melting ( p  < 0.05) at higher inclusion levels. Extruder back pressure, motor torque, and SME decreased with increasing TSG levels ( p  < 0.05) as the TSG effectively lowered the melt viscosity at high usage rates. The ER reached a maximum of 3.73 with a 2.5% TSG level extruded at 150 rpm ( p  < 0.05). The WAI of extrudates increased with TSG inclusion rate at equivalent SSs, whereas WSI behaved oppositely ( p  < 0.05). Small inclusions of TSG can improve the expansion properties of starch, whereas larger inclusions result in a lubrication effect that mitigates the shear‐induced depolymerization of starch. Practical Application: The impact of cold‐water soluble hydrocolloids, including tamarind seed gum, on the extrusion process, is poorly understood. From this work, tamarind seed gum effectively modifies the viscoelastic and thermal characteristics of corn starch in a way that enhances the direct expansion characteristics of the starch during extrusion processing. The effect is more beneficial at lower gum inclusion levels as higher levels result in reduced capabilities to translate shear from the extruder into useful transformations of the starch polymers during processing. Small amounts of tamarind seed gum could be used to improve the quality of extruded starch puff snacks.